1996
DOI: 10.1007/s004410050732
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of arg-vasotocin gene expressing neurons in the telencephalon and dorsal diencephalon of the domestic fowl. An immunocytochemical and in situ hybridization study

Abstract: A strong sex dimorphism in the distribution of immunoreactive arginine-vasotocin (AVT) and AVT mRNA was observed in telencephalic and dorsal diencephalic areas of the domestic fowl using immunocytochemistry and in situ hybridization. Two subgroups of immunoreactive parvocellular perikarya surrounded by dense plexus of immunoreactive fibres were found within the bed nucleus of the stria terminalis and the dorsal part of the diencephalic paraventricular region of males. No signs of immunoreactivity were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
49
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 39 publications
7
49
0
Order By: Relevance
“…These cells are detectable by immunocytochemistry in males only. This sex difference was also confirmed at the level of VT transcripts by ISH techniques (10,11).…”
Section: Sex Dimorphism Of the Vasotocin System In The Avian Brainmentioning
confidence: 53%
See 3 more Smart Citations
“…These cells are detectable by immunocytochemistry in males only. This sex difference was also confirmed at the level of VT transcripts by ISH techniques (10,11).…”
Section: Sex Dimorphism Of the Vasotocin System In The Avian Brainmentioning
confidence: 53%
“…In galliforms, immunocytochemical studies showed that VT-ir neurons are present in the BSTm of males only and cannot be visualized in females (10,11). In the canary this difference is less extreme, and both sexes have VT-ir neurons in the BSTm, but they are present in larger numbers in males than in females (6,13).…”
Section: Sex Dimorphism Of the Vasotocin System In The Avian Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual dimorphism in the distribution of arginine vasotocin (AVT)-or galanin-expressing neurons in chicken brain has been reported previously 26,27 . We examined the distribution of AVT mRNA-expressing neurons in the brains of WB chimeras and controls at 23-25 months and in the brains of FB chimeras at 8-11 months.…”
Section: Article Nature Communications | Doi: 101038/ncomms2372mentioning
confidence: 99%